Transgenerational entrepreneurship in entrepreneurial families: what is explicitly learned and what is successfully transferred?. Issue 5 (27th May 2021) - Dou, Junsheng; Su, Emma; Li, Shengxiao; Holt, Daniel T.
ABSTRACT: Research has suggested that the interaction between older and younger generation family members plays a pivotal role in the development of the younger generation's entrepreneurial practices. Little is known, however, what the older generation transfers to younger generation family members and what is explicitly applied by the younger generation in new entrepreneurial settings. Drawing on multiple case studies with Chinese business families, we identify the elements of knowledge that are passed between the two generations to include moral values, competence values, and cognitive heuristics. Moreover, we show that values rather than heuristics are further transferred in new entrepreneurial settings.